2013
DOI: 10.1128/jvi.00177-13
|View full text |Cite
|
Sign up to set email alerts
|

An Intact Sialoadhesin (Sn/SIGLEC1/CD169) Is Not Required for Attachment/Internalization of the Porcine Reproductive and Respiratory Syndrome Virus

Abstract: bSurface expression of SIGLEC1, also known as sialoadhesin or CD169, is considered a primary determinant of the permissiveness of porcine alveolar macrophages for infection by porcine reproductive and respiratory syndrome virus (PRRSV). In vitro, the attachment and internalization of PRRSV are dependent on the interaction between sialic acid on the virion surface and the sialic acid binding domain of the SIGLEC1 gene. To test the role of SIGLEC1 in PRRSV infection, a SIGLEC1 gene knockout pig was created by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
78
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 35 publications
1
78
0
Order By: Relevance
“…of wild-type pigs after infection with a type 2 virus (14). These results supported previous in vitro studies showing that PRRSV-resistant cell lines lacking surface CD169 and CD163 supported virus replication after transfection with a CD163 plasmid (15).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…of wild-type pigs after infection with a type 2 virus (14). These results supported previous in vitro studies showing that PRRSV-resistant cell lines lacking surface CD169 and CD163 supported virus replication after transfection with a CD163 plasmid (15).…”
supporting
confidence: 81%
“…Staining for surface expression of CD169 and CD163 was performed as described previously (14). Measurement of PRRS viremia.…”
Section: Methodsmentioning
confidence: 99%
“…However, one study showed that Sn gene knockout pigs were infected by PRRSV as usual (49), and a recent study using geneedited pigs demonstrates the indispensability of pCD163 (28). Therefore, pCD163 is a core receptor for PRRSV infection and requires more in-depth research.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work indicated a role of Siglec-1 as a receptor for infection of alveolar macrophages by porcine reproductive and respiratory syndrome virus. However, this was called into question in a study using Siglec-1 KO pigs (12). Both human and mouse Siglec-1 (mSiglec-1) expressed on human cells were recently shown to capture ecotropic murine leukemia virus (MLV), a simple retrovirus and mouse pathogen, in a ganglioside-dependent manner (13).…”
mentioning
confidence: 99%